Welcome to Westonci.ca, where finding answers to your questions is made simple by our community of experts. Connect with professionals ready to provide precise answers to your questions on our comprehensive Q&A platform. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently.
Sagot :
Alright, let's solve the equation step-by-step:
The given equation is:
[tex]\[ 8x - (2x - 13) = 36 \][/tex]
Step 1: Simplify inside the parentheses
First, we distribute the negative sign inside the parentheses:
[tex]\[ 8x - 2x + 13 = 36 \][/tex]
Step 2: Combine like terms
Next, we combine the [tex]\( x \)[/tex] terms:
[tex]\[ (8x - 2x) + 13 = 36 \][/tex]
[tex]\[ 6x + 13 = 36 \][/tex]
Step 3: Isolate the variable [tex]\( x \)[/tex]
To isolate [tex]\( x \)[/tex], we need to get rid of the constant term on the left side. Subtract 13 from both sides of the equation:
[tex]\[ 6x + 13 - 13 = 36 - 13 \][/tex]
[tex]\[ 6x = 23 \][/tex]
Step 4: Solve for [tex]\( x \)[/tex]
Now, divide both sides of the equation by 6 to solve for [tex]\( x \)[/tex]:
[tex]\[ x = \frac{23}{6} \][/tex]
So, the solution to the equation is:
[tex]\[ x = \frac{23}{6} \][/tex]
Step 5: Verify the solution
To ensure our solution is correct, we can plug [tex]\( x = \frac{23}{6} \)[/tex] back into the original equation and check if the left side equals the right side:
[tex]\[ 8 \left( \frac{23}{6} \right) - \left( 2 \left( \frac{23}{6} \right) - 13 \right) = 36 \][/tex]
Calculate each term:
[tex]\[ 8 \left( \frac{23}{6} \right) = \frac{184}{6} \][/tex]
[tex]\[ 2 \left( \frac{23}{6} \right) = \frac{46}{6} \][/tex]
[tex]\[ \frac{46}{6} - 13 = \frac{46}{6} - \frac{78}{6} = -\frac{32}{6} \][/tex]
[tex]\[ \frac{184}{6} - \left( -\frac{32}{6} \right) = \frac{184}{6} + \frac{32}{6} = \frac{216}{6} = 36 \][/tex]
Both sides are equal, which means our solution is correct.
Therefore, the correct choice is:
[tex]\[ \boxed{\{ \frac{23}{6} \}} \][/tex]
The given equation is:
[tex]\[ 8x - (2x - 13) = 36 \][/tex]
Step 1: Simplify inside the parentheses
First, we distribute the negative sign inside the parentheses:
[tex]\[ 8x - 2x + 13 = 36 \][/tex]
Step 2: Combine like terms
Next, we combine the [tex]\( x \)[/tex] terms:
[tex]\[ (8x - 2x) + 13 = 36 \][/tex]
[tex]\[ 6x + 13 = 36 \][/tex]
Step 3: Isolate the variable [tex]\( x \)[/tex]
To isolate [tex]\( x \)[/tex], we need to get rid of the constant term on the left side. Subtract 13 from both sides of the equation:
[tex]\[ 6x + 13 - 13 = 36 - 13 \][/tex]
[tex]\[ 6x = 23 \][/tex]
Step 4: Solve for [tex]\( x \)[/tex]
Now, divide both sides of the equation by 6 to solve for [tex]\( x \)[/tex]:
[tex]\[ x = \frac{23}{6} \][/tex]
So, the solution to the equation is:
[tex]\[ x = \frac{23}{6} \][/tex]
Step 5: Verify the solution
To ensure our solution is correct, we can plug [tex]\( x = \frac{23}{6} \)[/tex] back into the original equation and check if the left side equals the right side:
[tex]\[ 8 \left( \frac{23}{6} \right) - \left( 2 \left( \frac{23}{6} \right) - 13 \right) = 36 \][/tex]
Calculate each term:
[tex]\[ 8 \left( \frac{23}{6} \right) = \frac{184}{6} \][/tex]
[tex]\[ 2 \left( \frac{23}{6} \right) = \frac{46}{6} \][/tex]
[tex]\[ \frac{46}{6} - 13 = \frac{46}{6} - \frac{78}{6} = -\frac{32}{6} \][/tex]
[tex]\[ \frac{184}{6} - \left( -\frac{32}{6} \right) = \frac{184}{6} + \frac{32}{6} = \frac{216}{6} = 36 \][/tex]
Both sides are equal, which means our solution is correct.
Therefore, the correct choice is:
[tex]\[ \boxed{\{ \frac{23}{6} \}} \][/tex]
We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. Thank you for visiting Westonci.ca. Stay informed by coming back for more detailed answers.